(untitled) (Journal of Engineering Science, 2022)
With the increasing population, the pollution of the environmental elements is increasing day by day. Activated Carbon (AC) is solid, carbonaceous, non-hazardous, and highly porous complex compound and due to its adsorption property, this is widely used in the purification of various elements of the environment such as air, water, chemical, metal, etc. So, the enthusiasm in the production of activated carbon by the utilization of cheap agricultural and industrial wastes is growing rapidly. This study has been carried out to demonstrate the attempt of utilizing Rice Husk (RH) as it is abundantly available, environmentally friendly, low cost and a kind of renewable precursor material for the production of activated carbon. The muffle furnace assisted alkaline activation with potassium hydroxide (KOH) at different ratios was performed. The effects carbonization temperature of 500°C and 700°C and impregnation ratios were evaluated on the basis of yield, volatile matter, carbon content, and activation burn-off. All in all, lower carbonization temperature 500°C gives better results with higher yield of 13.24% and 7.3% activation bunroff at 1:1 carbon to KOH ratio. The increasing ratio also decreased the volatile substances and comparatively better results obtained at less burning temperature. Journal of Engineering Science 13(1), 2022, 105-112